CURRENT TRENDS IN THE SCIENTIFIC ORGANIZATION OF LABOR IN THE PROVISION OF MEDICAL SERVICES - Zakirova Gulnoza; Vaisov Dilshod (Ecominds Press, 2026)
This article provides a systematic analysis of current trends in the scientific organization of work in the provision of medical services. The study examines the impact of workload-based workload planning (WISN), time-motion analysis, lean healthcare methods (Lean Healthcare), the PDSA cycle and the Six Sigma methodology, as well as solutions based on digital technologies and artificial intelligence, on the activities of medical clinics. The results of the literature analysis show that the scientific organization of work is transforming from traditional approaches to a management model based on data, digitalization and focused on the human factor. These approaches make it possible to increase the efficiency of resource use in clinics, optimize patient flows, and redirect the time of medical staff directly to clinical activities. It is also substantiated that the integration of the competence approach to the division of labor and ensuring the well-being of employees into the system of scientific organization of labor contributes to the effective use of the professional potential of industry specialists and the consistent development of their qualifications. The conclusions of the study are of practical importance for making management decisions in the health care system based on empirical data and sustainable improvement of the activities of medical clinics.
Keywords: Scientific Labor Organization, Healthcare Services, Medical Clinic Management, Workload-Based Planning (WISN), Time and Movement Analysis, Lean Healthcare, PDSA, Digital Transformation, Artificial Intelligence, Healthcare Staff Qualifications.